2013
DOI: 10.1371/journal.ppat.1003710
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Trans-Sialidases as a Common Mediator of Endothelial Cell Activation by African Trypanosomes

Abstract: Understanding African Trypanosomiasis (AT) host-pathogen interaction is the key to an “anti-disease vaccine”, a novel strategy to control AT. Here we provide a better insight into this poorly described interaction by characterizing the activation of a panel of endothelial cells by bloodstream forms of four African trypanosome species, known to interact with host endothelium. T. congolense, T. vivax, and T. b. gambiense activated the endothelial NF-κB pathway, but interestingly, not T. b. brucei. The parasitic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…On the opposite end of the spectrum, normalization against B2M expression would intimate the notion of an escape mechanism from TNF-α induction taking place sometime between 2 and 6 hours post-induction ( Fig 1A ). Using the Normalization Factor, however, we show ICAM1 expression to be maximally induced 2h post TNF-α-treatment, and that the TNF-α-mediated induction is maintained at this level for the duration of the experiment ( Fig 1A ), consistent with previously reported ICAM1 induction kinetics in endothelial cells subjected to pro-inflammatory stimuli [ 100 , 101 ]. Together, and as may be surmised from a comparison of data in Figs 1 and 6 in which TNF-α either appeared to cause profound effects ( Fig 1A–1C ) or exerted modest gene modulation ( Fig 6A ), data normalization skewing was more pronounced in datasets in which gene expression modulation was moderate (for example here RLIP76 ).…”
Section: Resultssupporting
confidence: 91%
“…On the opposite end of the spectrum, normalization against B2M expression would intimate the notion of an escape mechanism from TNF-α induction taking place sometime between 2 and 6 hours post-induction ( Fig 1A ). Using the Normalization Factor, however, we show ICAM1 expression to be maximally induced 2h post TNF-α-treatment, and that the TNF-α-mediated induction is maintained at this level for the duration of the experiment ( Fig 1A ), consistent with previously reported ICAM1 induction kinetics in endothelial cells subjected to pro-inflammatory stimuli [ 100 , 101 ]. Together, and as may be surmised from a comparison of data in Figs 1 and 6 in which TNF-α either appeared to cause profound effects ( Fig 1A–1C ) or exerted modest gene modulation ( Fig 6A ), data normalization skewing was more pronounced in datasets in which gene expression modulation was moderate (for example here RLIP76 ).…”
Section: Resultssupporting
confidence: 91%
“…Ammar et al recently demonstrated that TconTS can induce activation of endothelial cells [ 36 ] and assumed that the TconTS-LD may be involved in this process. In this context, they prepared a mutant (Y438H) of TconTS1 (TcoTS-A1 according to their nomenclature) to prevent transfer activity.…”
Section: Discussionmentioning
confidence: 99%
“…Due to structural similarities with known lectins, it had been proposed [ 13 , 35 ] that TS LD binds carbohydrates and may play a role in mediating cell adhesion. Recently, Ammar et al suggested that TconTS lectin like domain binds sialic acids and is involved in endothelial cell activation [ 36 ]. However, to the best of our knowledge no direct evidence for carbohydrate-binding specificities of TS LD has been described.…”
Section: Introductionmentioning
confidence: 99%
“…Mab25 (mouse IgG2a, no dilution) labels a protein found all along the T. b. brucei axoneme (Pradel et al, 2006 ), while the monoclonal antibody L8C4 (mouse IgG1, no dilution) specifically recognizes T. b. brucei PFR2, localized throughout the PFR (Kohl et al, 1999 ). Anti-TS2 and anti-TS3 antibodies (rabbit polyclonal, 1/200) targeting T. vivax surface trans-sialidases (Ammar et al, 2013 ), calflagin antiserum (mouse, 1/500) that labels all proteins of the calflagin family (Giroud et al, 2009 ), and two VSG antisera (mouse, 1/500) raised against T. vivax variant surface glycoproteins (SG, unpublished material) were used to identify metacyclic and bloodstream trypomastigote parasites. For each antibody, IFA experiments were repeated on trypanosomes issued from at least 3 different experiments.…”
Section: Methodsmentioning
confidence: 99%